Ticari vekil - Sayın, Abdullah (My University, 2016)
Ticari vekil Türk Borçlar Kanunu 551-554 hükümleri arasında düzenlenmiştir. Ticari vekil, bir ticari işletmeyi işleten kişinin verdiği temsil yetkisini ifade eder. Ticari vekilin unsurları ticari işletme, sınırlı yönetim ve sınırlı temsil yetkisidir. Ticari vekil üçüncü kişiler karşısında TBK. 40. vd. anlamında temsilcidir. Ticari vekil işletme sahibi tarafından atanır. Yetkinin verilmesi kural olarak şekle bağlı değildir. Ticari vekile işletmenin bütün işleri için yetki verilebileceği gibi, belirli bazı işler için de yetki verilebilir. İlk halde genel yetkili ticari vekil, ikinci durumda ise özel yetkili ticari vekil söz konusu olur.Ticari işletme sahibi, ticari vekilin yetkilerini, üçüncü kişilere usulünce duyurulmuş olmak şartı ile sınırlandırabilir. Duyurunun gereğince yapılmış olup olmadığı dürüstlük kuralına göre belirlenir. Ticari vekilin temsil yetkisinin sona ermesi TBK. 554te düzenlenmiştir.

Commercial representative is regulated under Article 551-554 of the law on Turkish Code of Obligation. Commercial representive means representative authorization given by the person running a commercial undertaking. The element of a commercial representative is existence of a commercial undertaking, limited management authority, limited authority of representation. Commercial representative is a representative within the meaning of Article 40 of Turkish Code of Obligation when it comes to the relation between commercial agent and third parties. İn principle, commercial representative shall be appointed by the owner of the commercial undertaking. İn principle, an authorization to act as a commercial agent has no procedural requirements. A full authorization can be afforded to the commercial representative for all works of commercial undertaking. Likewise partial authorization can also be possible. In the first case, there is a fully authorized commercial agent at stake. In the second case, there is a specially authorized commercial representative in question. The owner of the commercial undertaking can limit the representative powers of the commercial representative on condition that he/ she duly announces it to third parties. Whether or not the announcement has been duly made shall be determined under the principle of honesty. The termination of the representative authority is regulated under Article 554 of the law on Turkish Code of Obligation.
Keywords: Kanuni temsil yetkisi; Özel hukuk; Türkiye